2023
DOI: 10.21203/rs.3.rs-2477090/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Engineered symbiotic bacteria interfering Nosema redox system inhibit microsporidia parasitism in honeybees

Abstract: Nosema ceranae is an intracellular parasite invading the midgut of honeybees, which causes serious nosemosis implicated in honeybee colony losses worldwide. The core gut microbiota is involved in protecting against parasitism, and the genetic engineering of the native gut symbionts provides a novel and efficient way to fight pathogens. Here, using laboratory-generated bees mono-associated with gut members, we find that Snodgrassella alvi inhibited microsporidia proliferation, potentially via the stimulation of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Additionally, adult workers removing infected larvae may transfer pathogens to healthy broods within colonies 67 and even between colonies through robbing and drifting 68 . Erban et al 12 showed that M. plutonius reached ~10 6 CFU/bee in the adult bees from colonies with clinical symptoms, which is 75-fold-higher than those from asymptomatic colonies. Our results showed that gnotobiotic bees mono-colonized with G. apis stain B14384H2 can achieve ~100-fold reduction of M. plutonius (on average, from 2.12 × 10 8 to 6.22 × 10 6 , p = 0.0079).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, adult workers removing infected larvae may transfer pathogens to healthy broods within colonies 67 and even between colonies through robbing and drifting 68 . Erban et al 12 showed that M. plutonius reached ~10 6 CFU/bee in the adult bees from colonies with clinical symptoms, which is 75-fold-higher than those from asymptomatic colonies. Our results showed that gnotobiotic bees mono-colonized with G. apis stain B14384H2 can achieve ~100-fold reduction of M. plutonius (on average, from 2.12 × 10 8 to 6.22 × 10 6 , p = 0.0079).…”
Section: Discussionmentioning
confidence: 99%
“…The colony loss has been described as multifactorial, involving combinations of environmental stress and infectious agents 3,4 . Honeybees are susceptible to various biological agents that cause disease, including eukaryotic 5,6 and prokaryotic pathogens 7 . Bacterial diseases are a significant contributing factor to the colony collapse disorder of honeybee populations 2 .…”
mentioning
confidence: 99%
“…Significant attention is paid to the application of Good Beekeeping Nosemosis and mortality in honeybees Practices as a form of prevention (Formato et al 2022). However, while these methods yield some results, they still prove insufficient , Holt and Grozinger 2016, Garrido et al 2023, Lang et al 2023, Prouty et al 2023. There is a pressing need for further research on N. ceranae, especially in the context of its effective control strategies that consider the microbiological safety of the hive products (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing engineered symbionts or bacteria to express and deliver dsRNA is an effective strategy for mediating insect physiological activities. 54,55 However, few studies have focused on mediating insect behavior through bacterial delivery of dsRNAs. A previous study of OBP from M. alternatus showed that feeding bacteria-expressed dsRNA can significantly repress the expression of OBP19 in adult M. alternatus.…”
Section: Discussionmentioning
confidence: 99%